Heterogeneity in MacMullin Number of Li-Ion Battery Electrodes Studied by Means of an Aperture Probe. Issue 1 (14th January 2022) - Liu, Baichuan; Prugue, Kayci; Nikpour, Mojdeh; Ward, Kristopher; Mazzeo, Brian A.; Wheeler, Dean R.
Abstract : Heterogeneity of MacMullin number within battery electrodes is a key metric affecting cell performance. To characterize this heterogeneity, an aperture probe was developed. This probe, coupled with a newly developed transmission-line model, allows for measurements of tortuosity, represented by the MacMullin number, on millimeter length scales. Local MacMullin number values of seven electrodes were measured, and the ionic resistance profiles of these electrodes are given through contour maps of the MacMullin number. The method is validated by comparing the average MacMullin number to the value obtained through other measurement methods. The results show significant local MacMullin number variation in such electrodes on a millimeter length scale. This method will allow battery manufacturers and researchers to better quantify sources of heterogeneity and improve electrode quality.